The length of vesicular stomatitis virus particles dictates a need for actin assembly during clathrin-dependent endocytosis. - David K Cureton; Ramiro H Massol; Sean P J Whelan; Tomas Kirchhausen (PLoS Pathogens)
Microbial pathogens exploit the clathrin endocytic machinery to enter host cells. Vesicular stomatitis virus (VSV), an enveloped virus with bullet-shaped virions that measure 70 x 200 nm, enters cells by clathrin-dependent endocytosis. We showed previously that VSV particles exceed the capacity of typical clathrin-coated vesicles and instead enter through endocytic carriers that acquire a partial clathrin coat and require local actin filament assembly to complete vesicle budding and internalization. To understand why the actin system is required for VSV uptake, we compared the internalization mechanisms of VSV and its shorter (75 nm long) defective interfering particle, DI-T. By imaging the uptake of individual particles into live cells, we found that, as with parental virions, DI-T enters via the clathrin endocytic pathway. Unlike VSV, DI-T internalization occurs through complete clathrin-coated vesicles and does not require actin polymerization. Since VSV and DI-T particles display similar surface densities of the same attachment glycoprotein, we conclude that the physical properties of the particle dictate whether a virus-containing clathrin pit engages the actin system. We suggest that the elongated shape of a VSV particle prevents full enclosure by the clathrin coat and that stalling of coat assembly triggers recruitment of the actin machinery to finish the internalization process. Since some enveloped viruses have pleomorphic particle shapes and sizes, our work suggests that they may use altered modes of endocytic uptake. More generally, our findings show the importance of cargo geometry for specifying cellular entry modes, even when the receptor recognition properties of a ligand are maintained.